2017
DOI: 10.1055/s-0037-1604473
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Hind and Mid-Foot Defects after Melanoma Resection Using the Reverse Sural Flap: A Case Series

Abstract: Background Melanoma resection creates important soft tissues defects, which are difficult to manage when located on the weight-bearing heel and mid foot. There is little evidence on the use of the reverse-flow sural flap for this type of reconstruction. Objective This study reports our case series on the reconstructive management of the hind and mid-foot defects after melanoma resection using the reverse sural artery flap. Materials and Methods This is a retrospective study of four cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…16 Larrañaga et al In his study of sural artery flap after resection of melanoma around heel found flap survival in all the cases with no recurrence at 5 year follow up. 17 Present study had 2 cases of SCC and 1 case of malignant melanoma and flap healed well in all the cases. Majority of the cases in our study was soft tissue defect after RTA and flap did well except one case of failure due to necrosis.…”
Section: Discussionmentioning
confidence: 63%
“…16 Larrañaga et al In his study of sural artery flap after resection of melanoma around heel found flap survival in all the cases with no recurrence at 5 year follow up. 17 Present study had 2 cases of SCC and 1 case of malignant melanoma and flap healed well in all the cases. Majority of the cases in our study was soft tissue defect after RTA and flap did well except one case of failure due to necrosis.…”
Section: Discussionmentioning
confidence: 63%
“…On reviewing the literature, we found that most of the RSAFs were done in cases of trauma and other nonmalignant causes[2526] though some authors[2127] have described it for melanoma of the foot. We have done RSAF for soft-tissue tumor and squamous cell carcinoma as well.…”
Section: Discussionmentioning
confidence: 99%
“…The main challenge when reconstructing surgical defects following the excision of acral melanoma on the foot is to preserve function. A range of flaps offering greater thickness and cushioning are frequently used in weight‐bearing areas 1,2 . Alternatives include secondary intention healing 3 and skin grafts 4 .…”
Section: Introductionmentioning
confidence: 99%
“…A range of flaps offering greater thickness and cushioning are frequently used in weightbearing areas. 1,2 Alternatives include secondary intention healing 3 and skin grafts. 4 Previous studies have suggested that dermal substitutes and STSGs may ease reconstruction by adding extra tissue to soften the impact on weightbearing areas.…”
Section: Introductionmentioning
confidence: 99%